2019
DOI: 10.1007/s00068-019-01171-9
|View full text |Cite
|
Sign up to set email alerts
|

Blunt cerebrovascular injury: incidence and long-term follow-up

Abstract: Purpose Blunt cerebrovascular injuries (BCVI), which can result in ischemic stroke, are identified in 1-2% of all blunt trauma patients. Computed tomography angiography (CTA) scanning has improved and is the diagnostic modality of choice in BCVI suspected patients. Data about long-term functional outcomes and the incidence of ischemic stroke after BCVI are limited. The aim of this study was to determine BCVI incidence in relation to imaging modality improvements and to determine long-term functional outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…1 A recent study demonstrated increased detection rates for BCVI in trauma patients from 0.3% in 2007 to 0.8% in 2016 after improvement of computed tomography angiography (CTA) scanning technique—increasing the slice number from 64 to 256 and increasing intravenous (IV) contrast injection rates from 3 to 6 mL/s—and the addition of CTA to the standard trauma CT protocol. 5 After introduction of a standardized screening criteria in 2007 in Australia, BCVI detection rates increased 2-fold from 0.52% to 1.06%. 4 More recent data report a 3% incidence of BCVI 7 in trauma patients, 3.8% incidence of TVAI in geriatric trauma patients, 8 8.5% incidence in patients with cervical trauma, 5 and up to 9% incidence of BCVI in patients with severe head injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A recent study demonstrated increased detection rates for BCVI in trauma patients from 0.3% in 2007 to 0.8% in 2016 after improvement of computed tomography angiography (CTA) scanning technique—increasing the slice number from 64 to 256 and increasing intravenous (IV) contrast injection rates from 3 to 6 mL/s—and the addition of CTA to the standard trauma CT protocol. 5 After introduction of a standardized screening criteria in 2007 in Australia, BCVI detection rates increased 2-fold from 0.52% to 1.06%. 4 More recent data report a 3% incidence of BCVI 7 in trauma patients, 3.8% incidence of TVAI in geriatric trauma patients, 8 8.5% incidence in patients with cervical trauma, 5 and up to 9% incidence of BCVI in patients with severe head injury.…”
Section: Discussionmentioning
confidence: 99%
“…The in-hospital mortality rate from 2005 to 2016 was 8% to 10.2% and the ischemic stroke rate was 23% to 28%. 5,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracranial traumatic vascular injury is present in approximately 1% to 2% of patients after blunt trauma, and the incidence of extracranial ICA injury ranges from 0.08 to 0.33%, among which 52-79% of these patients are asymptomatic. For most of these patients, conservative medical treatment is sufficient [2,[6][7][8][9][10]. However, for a small number of patients with disastrous implications, surgical intervention is needed [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a study from the Netherlands, Hundersmarck et al demonstrated that patients with BCVIs have worse long-term functional outcomes than those in the general trauma population. 16 In addition, patients with BCVI and ischemic stroke had worse long-term outcomes in terms of mobility and self-care than patients with BCVI alone. Patients with BCVI and traumatic brain injury had worse cognitive outcomes.…”
Section: Introductionmentioning
confidence: 99%